2009
DOI: 10.1055/s-2008-1039061
|View full text |Cite
|
Sign up to set email alerts
|

Histological Changes in Neonatal Kidneys after Cardiopulmonary Bypass and Deep Hypothermic Circulatory Arrest

Abstract: Although changes in the kidney tissue of newborn piglets are detectable after any cardiac procedure, changes are more profound after cardiopulmonary bypass with mild hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…Compared to control animals, a significant increase in renal tubular damage and loss of tubular function was observed. Previous work by Tirilomis et al [ 20 ] showed similar results after MHCA using a similar histological scoring system for kidney damage in neonatal piglets. Furthermore, an association between hemolysis, renal hypoxia, and acute kidney damage has been postulated [ 21 23 ].…”
Section: Discussionsupporting
confidence: 64%
“…Compared to control animals, a significant increase in renal tubular damage and loss of tubular function was observed. Previous work by Tirilomis et al [ 20 ] showed similar results after MHCA using a similar histological scoring system for kidney damage in neonatal piglets. Furthermore, an association between hemolysis, renal hypoxia, and acute kidney damage has been postulated [ 21 23 ].…”
Section: Discussionsupporting
confidence: 64%
“…However, there is some evidence that a more physiological pulsatile flow might be superior over the commonly used non-pulsatile flow during CPB (Kusch et al, 2001 ). Other organs like kidney, liver, and intestine are less tightly autoregulated, and thus also possibly affected by CPB, especially in young organisms (Tirilomis et al, 2009 , 2013 ; Doguet et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In experimental animal models of hypoxia, only minor histological changes, including mild brush border loss and vacuolization of tubular cells, are present in the kidney at 22 h post-peritonitis-induced septic shock in pigs [17] . Piglets subjected to mild hypothermic cardiopulmonary bypass exhibit tubular dilatation, vacuoles, leukocyte infiltration, epithelial destruction and interstitial oedema [18] . In cultured glomerular endothelial cells, hypoxia has been shown to induce apoptosis [19] .…”
Section: Introductionmentioning
confidence: 99%